EFEKTIVITAS BUKU CERITA BERGAMBAR UNTUK MENINGKATKAN MINAT BACA ANAK DISLEKSIA - Latifah Khairiyah1; Gustina Erlianti (JURNAL STIE SEMARANG, 2020)
This article aims to determine the effectiveness of picture story books on increasing reading interest in dyslexic children in Muhammadiyah Pauh IX Slb. This type of research is a qualitative approach in the form of descriptive. The research location is in Muhammadiyah Pauh IX. Research subjects were teacher and dyslexic children. The interview instruments used were interviews, observation and documentation. The results showed that: (a) dyslexic children need to be taught the concept of space before children recognize letters. The concept of space itself is the initial foundation of dyslexic children to be able to recognize letters, (b) the effectiveness of picture books for dyslexic children is very helpful to foster reading interest in dyslexic children, (c) solutions to dyslexic children to picture story books very much support children not to be lazy reading (d) the observations found that children love to use picture story books. This is very influential on reading interest in dyslexic children. If this is applied, the child can recognize letters well. Thus, picture books need to be introduced to children with dislection to assist in letter recognition.